Preparation method and application of multifunctional flexible FeCo PBA (at) MF device with microwave absorption and low infrared emission

By combining magnetoelectric double loss foam structure with metal-like materials, a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission is prepared, which solves the problem that the prior art is difficult to meet the absorption and reflection control of microwave and infrared bands. , realizes effective absorption and reflection control of microwave and infrared bands, and is suitable for a variety of application scenarios.

CN119220085AActive Publication Date: 2024-12-31NAT UNIV OF DEFENSE TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411341492.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing single-band wave absorbing materials are difficult to meet the needs of multifunctional composite materials for microwave absorption and low infrared emission, and cannot effectively control the absorption and reflection of microwave and infrared bands.

Method used

Combining magnetoelectric double loss foam structure and metal-like infrared low emissivity materials, a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission is prepared. By combining melamine carbide foam and FeCo PBA magnetic particles, silk printing is used Transparent conductive ink is processed to achieve absorption and reflection control of microwave and infrared bands.

Benefits of technology

It realizes effective absorption and reflection control of microwave and infrared bands, and has the characteristics of lightness, softness, good wave absorption performance and low infrared emissivity. It is suitable for aerospace, medical devices and electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220085A_ABST
    Figure CN119220085A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a microwave absorption and low infrared emission multifunctional flexible device, in particular to a preparation method and application of a microwave absorption and low infrared emission multifunctional flexible device. The method comprises the following steps: 1, preparing carbonized melamine foam; 2, preparing a FeCo PBA precursor; 3, preparing FeCo PBA powder with a magnetoelectric double-loss hollow structure; 4, preparing a product I; and 5, preparing the multifunctional flexible FeCo PBA-MF device with microwave absorption and low infrared emission, the multifunctional flexible FeCo PBA-MF device has the characteristics of lightness, thinness, softness, good wave absorption performance, low infrared emissivity and the like, when the thickness of the FeCo PBA-MF device is 2.0 mm and the frequency is 10.77 GHz, the minimum reflection loss reaches-70.37 dB, the maximum effective wave absorption bandwidth reaches 4.21 GHz, the FeCo PBA-MF device shows excellent wave absorption performance, and in the aspect of infrared performance, the microwave absorption and low infrared emission functions of the FeCo PBA-MF device are greatly improved. And the minimum emissivity of the wave band of 8-12 microns is 0.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a microwave absorption and low infrared emission multifunctional flexible device. Background Art

[0002] With the rapid development of wireless communication technology, especially the progress of next-generation networks, electronic technology and artificial intelligence, it has provided great convenience for people's daily lives, but it has also caused harmful electromagnetic pollution problems. In order to solve this problem, it is particularly important to develop a high-performance absorbing material. The absorbing material can absorb and attenuate electromagnetic waves, which is of great significance for eliminating electromagnetic radiation.

[0003] However, single-band absorbing materials are usually only suitable for specific frequency bands, and it is difficult to meet the current demand for new multifunctional composite materials with microwave absorption and low infrared emission. Therefore, the present invention will introduce infrared low-emissivity materials with metal-like properties on the basis of the above-mentioned magneto-electric double-loss foam structure composite absorbing materials, combine them with the foam structure absorbing materials, and comprehensively consider the absorbing characteristics, reflection characteristics and emission characteristics to prepare a new multifunctional device to achieve effective absorption and reflection control of microwave and infrared bands. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a preparation method and application of a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission.

[0005] A method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission is specifically completed by the following steps:

[0006] 1. Preparation of carbonized melamine foam:

[0007] The melamine foam is heated to 600° C. to 900° C., and carbonized at 600° C. to 900° C. for a period of time to obtain the carbonized melamine foam;

[0008] 2. Preparation of FeCo PBA precursor:

[0009] ①. Add iron salt to water and stir magnetically for a period of time to obtain an iron salt solution;

[0010] The iron salt described in step 2① is K 3 [Fe(CN) 6 ] or FeCl 3 ;

[0011] ②, add cobalt salt to the iron salt solution, then add sodium citrate and polyvinyl pyrrolidone, stir magnetically for a period of time, then centrifuge, wash, and dry to obtain FeCo PBA precursor;

[0012] The cobalt salt described in step 2② is Co(NO 3 ) 2 6H 2 O or CoCl 2 6H 2 O;

[0013] 3. Heating the FeCo PBA precursor to 600°C to 900°C, and carbonizing it at 600°C to 900°C for a period of time to obtain a magneto-electric double-loss hollow structure FeCo PBA powder;

[0014] Fourth, adding the magnetoelectric double loss hollow structure FeCo PBA powder into deionized water, ultrasonically dispersing it for a period of time, and then adding the aqueous polyurethane solution to obtain a mixed solution I; immersing the carbonized melamine foam into the mixed solution I, stirring the reaction, and finally taking out the carbonized melamine foam and drying it to obtain product I;

[0015] 5. Immerse product I in silk-screen transparent conductive ink, stir and react for a period of time, take out and dry to obtain a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission.

[0016] A multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission is used in aerospace, medical equipment, and electronic equipment.

[0017] Principle and effect of the present invention:

[0018] 1. The present invention provides a method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission. The melamine (MF) foam structure has a three-dimensional conductive network, which provides good impedance matching and dielectric loss. The FeCo PBA magnetic particles provide magnetic loss. The two work together to produce interface polarization and multiple attenuation mechanisms to enhance microwave absorption. The screen-printed transparent conductive ink described in step 5 is developed based on a conductive polymer (PEDOT:PSS), and the model is N3870. PEDOT:PSS is a conductive polymer material with metal-like properties, which not only has low emissivity but also has good conductivity. It is loaded on the surface of a magnetoelectric double-loss foam structure absorbing material to achieve compatibility between microwave absorption and low infrared emission.

[0019] 2. A multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission prepared by the present invention has the characteristics of lightness, softness, good wave absorption performance, and low infrared emissivity. When the thickness of the FeCo PBA@MF device is 2.0 mm and the frequency is 10.77 GHz, the minimum reflection loss reaches -70.37 dB, and the maximum effective wave absorption bandwidth reaches 4.21 GHz, showing excellent wave absorption performance; in terms of infrared performance, the minimum emissivity in the 8-12 μm band is 0.5;

[0020] 3. A multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission prepared by the present invention is used in aerospace, medical equipment, and electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a photo of the multifunctional flexible FeCo PBA-2@MF device with microwave absorption and low infrared emission prepared in Example 2;

[0022] Figure 2 SEM images, (a) is FeCo PBA-1@MF, (b) is FeCo PBA-2@MF, (c) is FeCo PBA-3@MF, (d) is a low-magnification image of FeCo PBA-2@MF, (e) is MF, and (f) is a high-magnification image of FeCo PBA-2@MF;

[0023] Figure 3 The three-dimensional reflection loss diagram and the two-dimensional reflection loss diagram of FeCo PBA-2@MF, (a) is the three-dimensional reflection loss diagram, (b) is the two-dimensional reflection loss diagram;

[0024] Figure 4 Infrared thermal imaging images of FeCo PBA-1@MF, FeCo PBA-2@MF, and FeCo PBA-3@MF devices. In the figure, Sample 1 is FeCo PBA-1@MF, Sample 2 is FeCo PBA-2@MF, and Sample 3 is FeCo PBA-3@MF. DETAILED DESCRIPTION

[0025] Specific implementation method 1: This implementation method is a method for preparing a multifunctional flexible FeCoPBA@MF device with microwave absorption and low infrared emission, which is specifically completed in the following steps:

[0026] 1. Preparation of carbonized melamine foam:

[0027] The melamine foam is heated to 600° C. to 900° C., and carbonized at 600° C. to 900° C. for a period of time to obtain the carbonized melamine foam;

[0028] 2. Preparation of FeCo PBA precursor:

[0029] ①. Add iron salt to water and stir magnetically for a period of time to obtain an iron salt solution;

[0030] The iron salt described in step 2① is K 3 [Fe(CN) 6 ] or FeCl 3 ;

[0031] ②, add cobalt salt to the iron salt solution, then add sodium citrate and polyvinyl pyrrolidone, stir magnetically for a period of time, then centrifuge, wash, and dry to obtain FeCo PBA precursor;

[0032] The cobalt salt described in step 2② is Co(NO 3 ) 2 6H 2 O or CoCl 2 6H 2 O;

[0033] 3. Heating the FeCo PBA precursor to 600°C to 900°C, and carbonizing it at 600°C to 900°C for a period of time to obtain a magneto-electric double-loss hollow structure FeCo PBA powder;

[0034] Fourth, adding the magnetoelectric double loss hollow structure FeCo PBA powder into deionized water, ultrasonically dispersing it for a period of time, and then adding the aqueous polyurethane solution to obtain a mixed solution I; immersing the carbonized melamine foam into the mixed solution I, stirring the reaction, and finally taking out the carbonized melamine foam and drying it to obtain product I;

[0035] 5. Immerse product I in silk-screen transparent conductive ink, stir and react for a period of time, take out and dry to obtain a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission.

[0036] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the thickness of the melamine foam in step 1 is 1 mm to 5 mm; the carbonization time in step 1 is 2 h to 3 h; the heating rate in step 1 is 5 ° C / min to 7 ° C / min. The other steps are the same as those in specific implementation method 1.

[0037] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: the mass ratio of the iron salt to the volume of water in step 2① is (200mg-400mg):100mL; the magnetic stirring time in step 2① is 5min-60min. The other steps are the same as those in specific implementation method 1 or 2.

[0038] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the mass ratio of the cobalt salt, sodium citrate and polyvinyl pyrrolidone described in step 2 ② is (100mg~1000mg):(500mg~1000mg):(500mg~1000mg); the volume ratio of the mass of the cobalt salt described in step 2 ② to the iron salt solution is (100mg~1000mg):(80mL~120mL); the magnetic stirring time described in step 2 ② is 15h~24h. The other steps are the same as those of specific embodiments 1 to 3.

[0039] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the centrifugal speed in step 2 ② is 5000 rpm to 10000 rpm; the washing in step 2 ② is performed with deionized water, and the number of washings is 3 to 5 times; the drying temperature in step 2 ② is 50° C. to 80° C. The other steps are the same as those in specific embodiments 1 to 4.

[0040] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that: the heating rate in step 3 is 5°C / min to 7°C / min; the carbonization time in step 3 is 2h to 3h. The other steps are the same as those in specific implementation methods 1 to 5.

[0041] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that the mass ratio of the magnetoelectric double loss hollow structure FeCo PBA powder described in step 4 to the volume ratio of deionized water is (5mg-20mg):(5mL-30mL); the volume ratio of the aqueous polyurethane solution described in step 4 to deionized water is (1mL-10mL):(5mL-30mL); the ultrasonic dispersion time described in step 4 is 5min-7min. The other steps are the same as specific embodiments 1 to 6.

[0042] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the stirring reaction time in step four is 20 minutes to 60 minutes; the drying temperature in step four is 30°C to 50°C, and the drying time is 5 minutes to 30 minutes; the mass fraction of polyurethane in the aqueous polyurethane solution in step four is 27% to 37%, which is purchased from Shenzhen Yoshida Chemical Co., Ltd. The other steps are the same as specific embodiments one to seven.

[0043] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the mass ratio of the product I described in step 5 to the volume ratio of the screen-printed transparent conductive ink is (0.15g to 0.4g): (0.1mL to 0.5mL); the screen-printed transparent conductive ink described in step 5 is developed based on a conductive polymer (PEDOT:PSS), model N3870, purchased from Shenzhen Yilai Technology Co., Ltd.; the stirring reaction time described in step 5 is 10min to 20min; the drying temperature described in step 5 is 50℃ to 80℃. The other steps are the same as specific embodiments 1 to 8.

[0044] Specific embodiment ten: This embodiment is a multifunctional flexible FeCoPBA@MF device with microwave absorption and low infrared emission, which is used in aerospace, medical equipment, and electronic equipment.

[0045] The following examples are used to verify the beneficial effects of the present invention:

[0046] Example 1: A method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission is specifically completed by the following steps:

[0047] 1. Preparation of carbonized melamine foam:

[0048] The melamine foam with a thickness of 5 mm was heated to 700° C. and carbonized at 700° C. for 2 h to obtain the carbonized melamine foam;

[0049] The heating rate in step 1 is 6°C / min;

[0050] 2. Preparation of FeCo PBA precursor:

[0051] ①. Add iron salt to water and stir magnetically for a period of time to obtain an iron salt solution;

[0052] The iron salt described in step 2① is K 3 [Fe(CN) 6 ];

[0053] The mass ratio of the iron salt described in step 2① to the volume ratio of water is 329 mg:100 mL;

[0054] The magnetic stirring time in step 2① is 30 min;

[0055] ②, add cobalt salt to the iron salt solution, then add sodium citrate and polyvinyl pyrrolidone, stir magnetically for a period of time, then centrifuge, wash, and dry to obtain FeCo PBA-1 precursor;

[0056] The cobalt salt described in step 2② is Co(NO 3) 2 6H 2 O;

[0057] The mass ratio of the cobalt salt, sodium citrate and polyvinyl pyrrolidone described in step 2② is 436.5mg800mg:800mg;

[0058] The volume ratio of the cobalt salt described in step 2② to the iron salt solution is 500 mg:100 mL;

[0059] The magnetic stirring time described in step 2② is 18h;

[0060] The centrifugal speed in step 2② is 5000 rpm;

[0061] The washing in step 2② is performed by washing with deionized water, and the number of washing times is 3 times;

[0062] The drying temperature in step 2② is 60°C;

[0063] 3. The FeCo PBA-1 precursor was heated to 700°C and carbonized at 700°C for 2h to obtain a magneto-electric double-loss hollow structure FeCo PBA-1 powder;

[0064] The heating rate in step 3 is 6°C / min;

[0065] Fourth, adding the magnetoelectric double loss hollow structure FeCo PBA-1 powder into deionized water, ultrasonically dispersing it for a period of time, and then adding the aqueous polyurethane solution to obtain a mixed solution I; immersing the carbonized melamine foam into the mixed solution I, stirring the reaction, and finally taking out the carbonized melamine foam and drying it to obtain product I;

[0066] The mass fraction of polyurethane in the aqueous polyurethane solution described in step 4 is 30%, which is purchased from Shenzhen Yoshida Chemical Co., Ltd.;

[0067] The mass ratio of the magnetoelectric double loss hollow structure FeCo PBA-1 powder described in step 4 to the volume ratio of deionized water is 10 mg:15 mL;

[0068] The volume ratio of the aqueous polyurethane solution to deionized water in step 4 is 5 mL:20 mL;

[0069] The ultrasonic dispersion time in step 4 is 6 minutes;

[0070] The stirring reaction time in step 4 is 40 min;

[0071] The drying temperature in step 4 is 40°C and the drying time is 10 minutes;

[0072] Fifth, the product I was immersed in a screen-printed transparent conductive ink, stirred and reacted for a period of time, and then taken out and dried to obtain a multifunctional flexible FeCo PBA-1@MF device with microwave absorption and low infrared emission;

[0073] The mass ratio of the product I described in step 5 to the volume ratio of the screen-printed transparent conductive ink is 0.287 g:0.1 mL;

[0074] The screen-printed transparent conductive ink described in step 5 is developed based on a conductive polymer (PEDOT:PSS), model N3870, and was purchased from Shenzhen Yilai Technology Co., Ltd.;

[0075] The stirring reaction time in step 5 is 10 min;

[0076] The drying temperature in step 5 is 50°C.

[0077] When the frequency of the multifunctional flexible FeCo PBA-1@MF device with microwave absorption and low infrared emission prepared in Example 1 is 8.2 GHz, the minimum reflection loss reaches -18.4 dB.

[0078] Example 2: The difference between this example and Example 1 is that the mass ratio of the cobalt salt, sodium citrate and polyvinyl pyrrolidone described in step 2② is 654.75mg:800mg:800mg; step 3 obtains the magnetoelectric double loss hollow structure FeCoPBA-2 powder; step 5 obtains the multifunctional flexible FeCo PBA-2@MF device with microwave absorption and low infrared emission. The other steps and parameters are the same as those in Example 1.

[0079] Example 3: The difference between this example and Example 1 is that the mass ratio of the cobalt salt, sodium citrate and polyvinyl pyrrolidone described in step 2② is 873mg:800mg:800mg; step 3 obtains the magnetoelectric double loss hollow structure FeCo PBA-3 powder; step 5 obtains the multifunctional flexible FeCo PBA-3@MF device with microwave absorption and low infrared emission. The other steps and parameters are the same as those in Example 1.

[0080] When the frequency of the multifunctional flexible FeCo PBA-3@MF device with microwave absorption and low infrared emission prepared in Example 3 is 12.4 GHz, the minimum reflection loss reaches -12.55 dB.

[0081] Figure 2SEM images, (a) is FeCo PBA-1@MF, (b) is FeCo PBA-2@MF, (c) is FeCo PBA-3@MF, (d) is a low-magnification image of FeCo PBA-2@MF, (e) is MF, and (f) is a high-magnification image of FeCo PBA-2@MF;

[0082] from Figure 2 As can be seen from (a), (b), and (c), the carbonized FeCo PBA is a uniformly dispersed cubic hollow particle; (e) shows that the FeCo PBA particles are tightly attached to MF.

[0083] Figure 3 The three-dimensional reflection loss diagram and the two-dimensional reflection loss diagram of FeCo PBA-2@MF, (a) is the three-dimensional reflection loss diagram, (b) is the two-dimensional reflection loss diagram;

[0084] from Figure 3 It can be seen that the multifunctional flexible FeCo PBA-2@MF device with microwave absorption and low infrared emission has a minimum reflection loss of -70.37dB and a maximum effective absorption bandwidth of 4.21GHz at a diameter of 2.0mm and a frequency of 10.77GHz, covering the entire X-band, showing good absorption performance.

[0085] Figure 4 Infrared thermal imaging images of FeCo PBA-1@MF, FeCo PBA-2@MF, and FeCo PBA-3@MF devices. Sample 1 is FeCo PBA-1@MF, Sample 2 is FeCo PBA-2@MF, and Sample 3 is FeCo PBA-3@MF.

[0086] from Figure 4 It can be seen that when three different proportions of FeCo PBA@MF are placed on a heating plate at 53°C, they still have infrared heat insulation effect after 2 hours, and the minimum emissivity of FeCo PBA@MF-2 in the 8-12μm band is 0.5.

Claims

1. A method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of carbonized melamine foam: The melamine foam is heated to 600° C. to 900° C., and carbonized at 600° C. to 900° C. for a period of time to obtain the carbonized melamine foam; 2. Preparation of FeCo PBA precursor: ①. Add iron salt to water and stir magnetically for a period of time to obtain an iron salt solution; The iron salt described in step 2① is K3[Fe(CN)6] or FeCl3; ②, add cobalt salt to the iron salt solution, then add sodium citrate and polyvinyl pyrrolidone, stir magnetically for a period of time, then centrifuge, wash, and dry to obtain FeCo PBA precursor; The cobalt salt described in step 2② is Co(NO3)2 6H2O or CoCl2 6H2O; 3. Heating the FeCo PBA precursor to 600°C to 900°C, and carbonizing it at 600°C to 900°C for a period of time to obtain a magneto-electric double-loss hollow structure FeCo PBA powder; Fourth, adding the magnetoelectric double loss hollow structure FeCo PBA powder into deionized water, ultrasonically dispersing it for a period of time, and then adding the aqueous polyurethane solution to obtain a mixed solution I; immersing the carbonized melamine foam into the mixed solution I, stirring the reaction, and finally taking out the carbonized melamine foam and drying it to obtain product I; 5. Immerse product I in screen-printed transparent conductive ink, stir and react for a period of time, take out and dry to obtain a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission.

2. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The thickness of the melamine foam in step 1 is 1 mm to 5 mm; the carbonization time in step 1 is 2 h to 3 h; the heating rate in step 1 is 5° C. / min to 7° C. / min.

3. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The mass ratio of the iron salt described in step 2① to the volume ratio of water is (200mg~400mg):100mL; the time of the magnetic stirring described in step 2① is 5min~60min.

4. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The mass ratio of the cobalt salt, sodium citrate and polyvinyl pyrrolidone described in step 2② is (100mg~1000mg):(500mg~1000mg):(500mg~1000mg); the volume ratio of the mass of the cobalt salt described in step 2② to the iron salt solution is (100mg~1000mg):(80mL~120mL); the time of magnetic stirring described in step 2② is 15h~24h.

5. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The centrifugal speed described in step 2② is 5000rpm~10000rpm; the washing described in step 2② is to use deionized water for cleaning, and the number of washing times is 3 times~5 times; the drying temperature described in step 2② is 50℃~80℃.

6. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The heating rate in step 3 is 5°C / min to 7°C / min; the carbonization time in step 3 is 2h to 3h.

7. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The mass ratio of the magnetoelectric double-loss hollow structure FeCo PBA powder described in step 4 to the volume ratio of deionized water is (5mg~20mg):(5mL~30mL); the volume ratio of the aqueous polyurethane solution described in step 4 to deionized water is (1mL~10mL):(5mL~30mL); the ultrasonic dispersion time described in step 4 is 5min~7min.

8. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The stirring reaction time in step 4 is 20 min to 60 min; the drying temperature in step 4 is 30° C. to 50° C., and the drying time is 5 min to 30 min; the mass fraction of polyurethane in the aqueous polyurethane solution in step 4 is 27% to 37%.

9. The method for preparing a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission according to claim 1, characterized in that The mass ratio of the product I described in step 5 to the volume ratio of the screen-printed transparent conductive ink is (0.15g~0.4g):(0.1mL~0.5mL); the screen-printed transparent conductive ink described in step 5 is developed based on a conductive polymer (PEDOT:PSS), and the model is N3870; the stirring reaction time described in step 5 is 10min~20min; the drying temperature described in step 5 is 50℃~80℃.

10. Application of a multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission prepared by the preparation method according to claim 1, characterized in that A multifunctional flexible FeCo PBA@MF device with microwave absorption and low infrared emission is used in aerospace, medical equipment, and electronic equipment.

Citation Information

Patent Citations

  • Preparation method of polyaniline / carbon foam composite material with controllable wave-absorbing property

    CN110256847A

  • Preparation method of cobalt-doped ferrite wave-absorbing material and wave-absorbing material

    CN111205818A

  • Composite electromagnetic wave-absorbing foam prepared from ZIF-67 / melamine and preparation method thereof

    CN111410194A

  • Multifunctional electromagnetic material with characteristics of high-frequency electromagnetic absorption and corrosion resistance as well as preparation method and application of multifunctional electromagnetic material

    CN115831515A

  • Preparation method of efficient wave-absorbing composite material CoFe-coated CNTs

    CN116161678A